ANALISIS LANDASAN FILOSOFIS PENDIDIKAN HUMANISTIK DALAM PENGEMBANGAN KARAKTER SISWA SEKOLAH DASAR - Zelfi Wahyuni; Maisyarah; Rizqi Kurniawan; Mardiati Neli Susanti; Hendrizal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the philosophical foundations of humanistic education as a basis for character development among elementary school students. In the midst of a character crisis affecting Indonesian young generation, marked by bullying, intolerance, and declining moral values, humanistic education offers a relevant paradigm that places students as active subjects with inherent potential for holistic growth. This library research employed a qualitative descriptive approach by systematically reviewing 30 SINTA-accredited journal articles published between 2022 and 2026. The findings reveal that humanistic education is grounded in three main philosophical pillars: existentialism emphasizing freedom and individual uniqueness, pragmatism highlighting authentic experiential learning, and perennialism integrating universal noble values. These foundations are effectively integrated with Ki Hadjar Dewantara’s philosophy and Pancasila values. The humanistic approach proved effective in developing five key character dimensions: religiosity, honesty, social concern, responsibility, and independence. This study proposes the Model of Indonesian Contextual Humanistic Education (PHKI) and recommends curriculum reconstruction aligned with the Merdeka Belajar policy. The results provide both theoretical contributions and practical implications for elementary education in Indonesia.